Robust control of a hip–joint rehabilitation robot. (May 2017) - Guzmán, Cesar H.; Blanco, Andrés; Brizuela, Jorge A.; Gómez, Fabio A.
Highlights: This paper presents the implementation of GPI control in a hip–joint rehabilitation robot. HipBot is the hip–joint rehabilitation robot proposed to obtain experimental results. GPI controllers rejected unknown disturbances and kept trajectory tracking tasks stable. Two healthy volunteers were recruited for the experimental tests. Experimental and simulation results corroborate the effectiveness and robustness of GPI control. Abstract: Physical therapy aimed at restoring patient limbs functionality after a stroke. Rehabilitation robotics has the potential to reduce the physical workload of physiotherapists. Despite research effort in advanced control methods, rehabilitation robot control is still a challenge. In this paper, a control strategy for a hip–joint rehabilitation robot based on generalized proportional integral (GPI) controllers is presented, and the performance of the control system has been evaluated by means of simulation and experimental results under different conditions, with particular attention to unknown disturbances and dynamic changes. Simulation and experimental results reported were compared and a good agreement was obtained. These findings can be useful for further designs of rehabilitation robots.